APPLICATION OF ANALYTICAL HIERARCHY PROCESS (AHP) METHOD TO DETERMINE THE SELECTION OF QUALITY WORK PACKAGES: A STUDY ON THE BUDGET PLAN OF PERUM PERURI KARAWANG - Ahmad Baihaqi, Kiki; Zonyfar, Candra; Sukenda (International Journal of Psychosocial Rehabilitation, 2020)
Implementation of the method of Analytical Hierarchy Process (AHP ) can be used to classify some fields such as that involving multiple choice, the research is involved to determine the RAB in an election the quality of the material the material and the work of development. Thus, obtained points packaged material what only the use and budget how alone are shown in a study of this could be a reference to election package workmanship in a project workmanship of building both the office and home, in terms of this home office. The results of testing the functions and needs of stakeholders using the User Acceptance Testing (UAT) method indicate the level of satisfaction and suitability of the stakeholders. Samples were taken throughout the part of the department that handles the work is that a number of 7 to 6 parameters of assessment.